Sociology 380: Social Network Analysis - Collom, Ed (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is designed to provide students with the opportunity to master the major concepts within the field of social networks. Social network theory should be of interest since it explains how our connections to other individuals, to organizations, and to major social institutions influence our actions and attitudes.